LEVELS OF KNOWLEDGE AND ATTITUDES TOWARD PERIODONTAL DISEASE AMONG PARENTS OF DENTAL STUDENTS - Mardha Ade Pritia; Megawati Prajarini; Ulia Dwi Ulma; Tsuraya Bilqis (Journal of Health and Dental Sciences, 2026)
Periodontal disease is a chronic condition with a high global burden that affects both oral and systemic quality of life. Epidemiological trends indicate a rising incidence and a strong association with systemic conditions such as diabetes mellitus and cardiovascular disease, positioning it as a significant public health concern with both clinical and preventive urgency. Preventive efforts are largely influenced by the level of public knowledge, attitudes, and behaviors toward periodontal health; however, a gap in the literature persists regarding family-level knowledge and attitudes, particularly among populations with close proximity to dental education institutions. Therefore, this study aims to analyze the level of knowledge and attitudes toward periodontal health among parents of dental students and to identify factors contributing to periodontal literacy. This study employs a quantitative approach with a cross-sectional design, in which data are collected using a structured questionnaire assessing knowledge, attitudes, and sociodemographic characteristics. Descriptive statistical analysis is applied to evaluate data distribution and examine relationships between variables. The expected outcomes include the provision of baseline data on periodontal literacy within family groups that have indirect access to academic information, as well as strategic recommendations for family-based educational interventions. Furthermore, the findings are anticipated to contribute to academic advancement through national or international scientific publications and to support the development of periodontal health promotion programs at both institutional and community levels. DOI : 10.54052/jhds.v6n1.p101-110